THE CONTRACT FOR THE RECRUITMENT AND EMPLOYMENT OF DOMESTIC WORKERS (STUDY IN UAELAW NO.10 OF 2017) - Researcher. Humaid Ali Majed Al Matrooshi, Dr. prof. Salihahmedluhaibi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The study focus on the relationship of the recruitment office for the employment of assistive workers with the worker and the relationship of the recruitment office for the employment of domestic workers with the employer without addressing the general rules such as the relationship of the employer and the worker. We are trying to take what is new in Federal Law No. 10 of 2017 regarding domestic workers and its implementing regulations, Cabinet Resolution No. 22 of 20195. Results of the study is several conclusions have been reached, which are :Not setting a definition for the domestic workers contract. Not attaching the contract form in the Domestic workers Law or its implementing regulations. Not to put a job description for the professions mentioned in the appendix to the Domestic workers Law. Recommendations of the researcher Through this research and after getting acquainted with the results, it can be said that there is a set of recommendations that we deem it necessary to follow, namely: The legislator must set a definition in which he clarifies the tripartite relationship that takes place in this contract and not only defining the employment contract, but rather clarifying this relationship. The legislator must attach a form of the contract in the Domestic workers Law or its executive regulations, since the contract is one of the formal contracts that the legislator has determined to be according to a model approved by the competent ministry